Design of photovoltaic power conditioning incorporating maximum power point tracking of solar cell - Syeed, Nuzhat Noor; Hossain, Ahmed Aaqib Sajjasd; Hasan, Nazmul; Bhiyan, Menhajul Abedin (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.